2004
DOI: 10.1002/anie.200460278
|View full text |Cite
|
Sign up to set email alerts
|

Rhodizonate Metal Complexes with a 2D Chairlike M6 Metal–Organic Framework: [M(C6O6)(bpym)(H2O)]⋅n H2O

Abstract: Two transition‐metal rhodizonate complexes, [M(C6O6)(bpym)(H2O)]⋅n H2O (M=Cd, n=1; M=Mn, n=2; bpym=2,2′‐bipyrimidine), are reported. Both the rhodizonate and bpym ligands are bis‐bidentate ligands (see the Cd example depicted) which chelate the metal ions, thus forming a novel 2D chairlike M6 metal–organic framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“… Coordination mode of literature known rhodizonato complexes [ M = Mn, Cd, L = bipyrimidine, water;8a M = Zn, L = tris(2‐pyridylmethyl)amine] 8b…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“… Coordination mode of literature known rhodizonato complexes [ M = Mn, Cd, L = bipyrimidine, water;8a M = Zn, L = tris(2‐pyridylmethyl)amine] 8b…”
Section: Resultssupporting
confidence: 67%
“…Until now only three other examples of rhodizonate transition metal complexes have been published. In 2004 Wang et al presented the first rhodizonate complexes with manganese and cadmium central atoms 8a. The rhodizonate anion acts as bridging ligand in a 1κ 2 O,O',2κ 2 O′′,O′′′ fashion leading to a 2D metal organic framework (under inclusion of bipyrimidine as additional bridging ligand).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, such a benzenehexaolate (C 6 O 6 6À ) ligand, to our knowledge, has never been reported in any organic compounds or transition-metal complexes and is observed here for the first time. [13] Unlike some similar chelating and bridging organic linkers, the bho 6À and pyridine-derived (Py-R n ) ligands favor the formation of a molecular bamboo-like structure, rather than a gondola, rectangle, or metalloprism. [14] A single-crystal X-ray diffraction analysis revealed that compound 1 crystallizes in the trigonal space group R " 3.…”
Section: Hexaolate Complexesmentioning
confidence: 99%
“…Thec ombination of these two ligands (bho 6À and acpy) is chemically and structurally compatible.I np articular, the bho 6À ligand was fortunately captured by six (CO) 3 Re I moieties and six N-donor ligands.Interestingly,such abenzenehexaolate (C 6 O 6 6À )l igand, to our knowledge,h as never been reported in any organic compounds or transition-metal complexes and is observed here for the first time. [13] Unlike some similar chelating and bridging organic linkers,the bho 6À and pyridine-derived (Py-R n )l igands favor the formation of am olecular bamboo-like structure,r ather than ag ondola, rectangle,o rmetalloprism. [14] As ingle-crystal X-ray diffraction analysis revealed that compound 1 crystallizes in the trigonal space group R " 3.…”
mentioning
confidence: 99%